Academic Leagues and medical formation: contributions and challenges - Albina Rodrigues Torres; Gabriel Martins de Oliveira; Fábio Massahito Yamamoto; Maria Cristina Pereira Lima; Philip Sidney Pacheco Badiz (Interface: Comunicação, Saúde, Educação, 2008)
There has been a considerable increase in the number of academic leagues active within undergraduate medical courses in Brazil over the last few years. However, this phenomenon has not been accompanied by adequate reflection on its determinants, on the role of the leagues within the institutions or even on their pedagogical function. From these observations, the authors analyze the scant literature on this topic, describe the experience of the academic leagues of Botucatu Medical School, Unesp, and reflect on the role of these leagues in medical training, in an attempt to partially fill this gap and contribute towards this important discussion.